Enormous, rapidly growing breast mass - Verma, Vivek (BMC Cancer, 2015)
BACKGROUND: Signs and symptoms of a rapidly enlarging breast mass are not only important for all clinicians to recognize and assess, but also are not uncommon occurrences. We describe a similar but unique case that developed into an enormous, 36 cm exophytic mass. CASE PRESENTATION: A 51-year-old woman with history of psychiatric conditions presented for signs and symptoms of sepsis. It was determined that the source was an enormous 36 cm mass originating from the breast/chest wall. After stabilizing the patient with antibiotics, she underwent successful resection. Surgical margins were positive, and histopathology demonstrated bland spindle cells with stromal overgrowth. Together with clinical and histopathological information, the patient was diagnosed with a phyllodes tumor. CONCLUSION: Differential diagnosis of rapidly growing breast masses is discussed, which are not uncommon occurrences in clinical medicine. One etiology, phyllodes tumors, can grow into large, exophytic masses as described. Oncologic treatment is discussed, usually consisting of surgery with postoperative radiotherapy for high-risk features.